Dysregulated hepatic UDP-glucuronosyltransferases and flavonoids glucuronidation in experimental colitis - Zeng, Wanying; Liu, Xiaojing; Wu, Yangyang; Cai, Yuting; Li, Zhennan; Ye, Fei; Sun, Yuanhong; Li, Feng; Xing, Huijie; Wang, Shuai (Frontiers in Pharmacology, 2022)
Glucuronidation catalyzed by UDP-glucuronosyltransferases (UGTs) is one of the most important phase II mechanisms, facilitating drug clearance via conjugation of glucuronic acid with polar groups of xenobiotics. Accumulating evidence suggests that IBDs impact drug disposition, but whether and how IBDs regulate UGTs and drug glucuronidation remains undefined. In this study, we aim to investigate gut inflammation on the expression of UGTs and drug glucuronidation. Given that glucuronidation occurs primarily in the liver, we analyzed the mRNA changes in hepatic UGTs with a DSS-induced mouse colitis model. Twelve UGTs were down-regulated in the liver of colitis mice including UGT1A1 and UGT1A9 (two representative UGTs). Colitis in mice down-regulated UGT1A1 and UGT1A9 in the liver but not in other metabolic tissues. We also established that the down-regulation of UGTs was attributed to the disease itself rather than the DSS compound. Moreover, colitis-reduced UGT1A1 and UGT1A9 lead to dampened baicalein and puerarin glucuronidation. PXR was the only UGT regulator significantly down-regulated in colitis mice, suggesting dysregulation of PXR is associated with the down-regulation of UGT1A1 and UGT1A9, thereby potentially resulting in dysfunction of baicalein and puerarin glucuronidation. Collectively, we established that UGTs and glucuronidation are dysregulated in colitis, and this effect may cause variation in drug responsiveness in IBDs.